Increasing awareness of climate change with immersive virtual reality - Thoma, Stefan P.; Hartmann, Matthias; Christen, Jonas; Mayer, Boris; Mast, Fred W.; Weibel, David (Frontiers in Virtual Reality, 2023)
Previous research has shown that immersive virtual reality (VR) is a suitable tool for visualizing the consequences of climate change. The aim of the present study was to investigate whether visualization in VR has a stronger influence on climate change awareness and environmental attitudes compared to traditional media. Furthermore, it was examined how realistic a VR experience has to be in order to have an effect. The VR experience consisted of a model of the Aletsch glacier (Switzerland) melting over the course of 220 years. Explicit measurements (new environmental paradigm NEP, climate change skepticism, and nature relatedness) and an implicit measurement (implicit association test) were collected before and after the VR intervention and compared to three different non-VR control conditions (video, images with text, and plain text). In addition, the VR environment was varied in terms of degrees of realism and sophistication (3 conditions: abstract visualization, less sophisticated realistic visualization, more sophisticated realistic visualization). The six experimental conditions (3 VR conditions, 3 control conditions) were modeled as mixed effects, with VR versus control used as a fixed effect in a mixed effects modeling framework. Across all six conditions, environmental awareness (NEP) was higher after the participants (N = 142) had been confronted with the glacier melting, while no differences were found for nature relatedness and climate change skepticism before and after the interventions. There was no significant difference between VR and control conditions for any of the four measurements. Nevertheless, contrast analyses revealed that environmental awareness increased significantly only for the VR but not for the control conditions, suggesting that VR is more likely to lead to attitude change. Our results show that exposure to VR environments successfully increased environmental awareness independently of the design choices, suggesting that even abstract and less sophisticated VR environment designs may be sufficient to increase pro-environmental attitudes.